(untitled) (Neo Science Peer Reviewed Journal, 2023)
V. O. Pelevin’s prose belongs to the postmodernist movement, there are many symbolic details in it, colorism plays a special role, but the semantization of color is quite unique. This article analyzes the symbolism of color in V.O. Pelevin’s story “The Green Box”.